Evaluating 2013-Curriculum Implementation on English Subject of Junior High School in Yogyakarta, Indonesia - Nanik Supriani; Hanandyo Dardjito; Endah Kunti Istiqomah (Universitas Sarjanawiyata Tamansiswa, 2019)
The purpose of this study was to evaluate the implementation of 2013 - curriculum of English in three junior high schools in Yogyakarta, Indonesia. Evaluation is carried out by applying the Context, Input, Process and Product (CIPP) Model. This study invited a volunteer of a curriculum development expert, English teachers, and students to be the participants. The analysis on the documents, observation, and interviews indicated that the basic competence and the core competence met the studentsâ€™ needs. This study also found that there were no criteria in regard with the targeted language form and the teaching learning process focused more on practicing in answering test drills to prepare the students for the national final exam. The findings indicated that students experienced difficulties with vocabulary they had never been taught at school and were challenged with long sentences while the test designer had problem in assessing text level of difficulties. Findings also showed that the studentsâ€™ proficiency was moderate.Â Keywords: content standard, CIPP Model, English subjects, evaluation, 2013 curriculum